(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Strengthening the capacity of Village-Owned Enterprises (BUMDesa) and Joint Village-Owned Enterprises (BumDesMa) is a strategic step toward building village businesses that are adaptable to digitalization and globally oriented. This program is designed to equip participants with the skills to analyze business feasibility, prepare company profiles, and apply business digitalization concepts as the foundation for developing competitive village businesses. The activities were carried out through the stages of needs identification, material design, interactive training, technical assistance, and pre-test and post-test-based evaluation. A total of 116 participants took part in the program. To measure the effectiveness of the training, the non-parametric Wilcoxon signed-rank test was applied, yielding a p-value of 0.00083. These results confirm that the training significantly improved participants’ ability to understand and apply the concepts taught. More significant than the numerical results, participants successfully produced business feasibility analysis documents and company profiles as concrete outputs that most BUMDesa and BumDesMa did not previously possess. This achievement reflects an increase in substantive capacity for professional planning and management of village businesses. The implications of this achievement confirm that strengthening document-based competencies can strengthen the foundation for business sustainability and enhance the competitiveness of BUMDesa and BumDesMa at both regional and global levels.